2017
DOI: 10.1242/dev.152967
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency non-mosaic CRISPR-mediated knock-in and indel mutation in F0 Xenopus

Abstract: The revolution in CRISPR-mediated genome editing has enabled the mutation and insertion of virtually any DNA sequence, particularly in cell culture where selection can be used to recover relatively rare homologous recombination events. The efficient use of this technology in animal models still presents a number of challenges, including the time to establish mutant lines, mosaic gene editing in founder animals, and low homologous recombination rates. Here we report a method for CRISPR-mediated genome editing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…Given the fact that about two-thirds of human genetic diseases arise from point mutations (15), the current homology-independent knock-in method in X. tropicalis is suboptimal for precise single-base editing (7,12). The homology-dependent knock-in of short DNA fragments using single-strand oligodeoxynucleotides as templates is based on the host transfer method, which is technically demanding (16).…”
mentioning
confidence: 99%
“…Given the fact that about two-thirds of human genetic diseases arise from point mutations (15), the current homology-independent knock-in method in X. tropicalis is suboptimal for precise single-base editing (7,12). The homology-dependent knock-in of short DNA fragments using single-strand oligodeoxynucleotides as templates is based on the host transfer method, which is technically demanding (16).…”
mentioning
confidence: 99%
“…Conflicting results have been obtained for both compounds in diverse cell types. SCR7 has been found to increase HDR efficiencies (Aslan, Tadjuidje, Zorn, & Cha, 2017; Chu et al, 2015; Hu et al, 2018; Li et al, 2017; Maruyama et al, 2015; Pinder et al, 2015; Robert et al, 2015; Singh et al, 2015), but no significant effects were observed by other groups or on other cell types (Aslan et al, 2017; Canny et al, 2018; Chu et al, 2015; Greco et al, 2016; Gutschner, Haemmerle, Genovese, Draetta, & Chin, 2016; Lee, Grav, Pedersen, Lee, & Kildegaard, 2016; Riesenberg & Maricic, 2018; Song et al, 2016; Xie et al, 2017; D. Yang et al, 2016; Zhang et al, 2017). Similarly, RS‐1 has been reported to both enhance targeted KI (Pan et al, 2016; Pinder et al, 2015; Song et al, 2016) and to not exert a positive effect (Riesenberg & Maricic, 2018; K. Wang et al, 2016; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, mutagenesis can be performed through microinjection of Cas9-encoding mRNA or of Cas9 protein together with sgRNA into fertilized embryos. Contrary to Cas9-encoding mRNA, RNPs are immediately active upon microinjection and are generally more effective in the fast dividing blastomeres of the zebrafish and Xenopus embryos (Figure 1) [37,38], in which mutagenesis occurring after the first cleavages leads to increased mosaicism. In plants, this DNA-free approach allows generation of marker-free ‘cisgenic’ variants that could be exempted from current GMO regulations and thereby supersede all the technologies of gene editing in plants [39].…”
Section: Delivery Methodsmentioning
confidence: 99%